Myoclonia congenita (trembling piglets) - H W Leipold; R Scarsi; D Schoneweis; R Milleret; R Phillips (Kansas Agricultural Experiment Station Research Reports, 1978)
An epidemiologic survey was conducted on ten swine farms in Kansas and two in Nebraska (1878 piglets in 251 litters) to determine the incidence, clinical signs, and cause of myoclonia corrgenita. The percentage of litters with myoclonia congenita was 37.45%, ranging from 4.35% to 100%. Morbidity rate was 37.5%, which is lower than rates in previous surveys in the United States. Mortality rate in all pigs was 17.73% while the fatality rate of affected pigs was 47.2%.; Swine Day, Manhattan, KS, November 9, 1978
Keywords: Swine day; 1978; Kansas Agricultural Experiment Station contribution; no. 79-105-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 342; Swine; Myoclonia congenita; Trembling piglets